ANALISIS BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SELULER XL PRABAYAR DI KABUPATEN BOGOR - Andri Budi Santosa; Berlia Najla (Institut Teknologi dan Bisnis Dewantara, 2022)
The purpose of this study was to determine the effect of product (product), price (price), promotion (promotion), place (place) partially and simultaneously and to find out what variables had the most dominant influence on purchasing decisions for prepaid XL cellular products in Bogor Regency. The sample used in this study was determined by the Rao Purba formula with a margin of error of 10% because the population is unknown. From the results of the t-test, it is known that on XL prepaid cellular products in Bogor district, it is known that there are no products and prices have a significant influence on purchasing decisions, while in promotions and places there is no significant influence on consumer purchasing decisions. According to the results of simultaneous testing (F test) shows that there is a joint influence between product, price, promotion, and place on purchasing decisions and according to the results of regression tests, product variables are the variables that have the most dominant influence on purchasing decisions.